FAMILY COMPLIANCE IN IMPLEMENTING HEALTH PROTOCOLS: FACTOR ANALYSIS OF KNOWLEDGE, VALUES AND BELIEFS INFECTING COVID-19 - Nasrudin -; Siti Urifah; Devin Prihaninuk (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2022)
Families are the main concern in efforts to handle thePandemic Coronavirus Disease 19 (COVID-19). Knowledge, values ​​and beliefs of contracting COVID-19 are very important in efforts to comply with the COVID-19 protocol. The purpose of this study was to analyze the relationship between knowledge and values and the application of health protocols in Jombang Regency. The research method uses descriptive analytic with a cross sectional approach. The population in this study were heads of families from 7 sub-districts in Jombang Regency, the sampling technique used was cluster sampling and the research sample consisted of 80 families. The results of the knowledge factor research with compliance show the results of P Value 0.649 > 0.05 which means there is no relationship between community knowledge and family compliance in carrying out the protocol health preventive COVID-19. The relationship between the belief value of being infected with family compliance in carrying out the health protocol prevention COVID-19 shows a P Value of 0.045 <0.05, which means there is a relationship. The conclusion of this study is that the values ​​and beliefs of families infected with COVID-19 have more influence on family compliance in implementing the COVID-19 prevention health protocol.